Strategi dan Peta Jalan Pencapaian Tujuan Pembangunan Berkelanjutan di Kota Serang - Nurfindarti, Erti (Jurnal Bina Praja, 2019)
The phenomenon of climate change and global warming is driving the issue of the Sustainable Development Goals developing in countries in the world, including Indonesia. Indonesia is incorporated in the Paris Agreement and follows up with the drafting of laws and regulations which form the basis for implementing TPB in the regions. Profile of achievement of the Serang City Sustainable Development Goals based on the KLJDD KLHS Document shows that there are still 92 indicators (50, 27%) that have not been achieved. Previous research on strategies and road maps to achieve TPB at the regional level is still limited and is the state of the art of this research. The method used is a sequential transformative strategy mix method that is integrated with the TAIDA method as a scenario planning method, by prioritizing qualitative research through literature studies, personal observations, discussions, interviews which are part of the initial process of the TAIDA (tracking, analyzing) method. Followed by quantitative research through descriptive statistics on weight and rating calculations to formulate strategies and road maps (the next process of the TAIDA method: identifying, deciding, acting). The results of this study are that the strategy to achieve TPB is focused on 4 (four) aspects, namely aspects of regulation (synchronization of regulations), funding (potential funding other than APBD along with preparation of regional financial mechanisms), socialization (aimed at the public and all stakeholders through sharing media) and collaboration (initiation of cooperation with all parties and other local governments). The road map consists of 9 (nine) stages, from socializing to promoting best practices.